Introduction - Denis Menjot (Mélanges de la Casa de Velázquez)
Of the manifold evaluations to which the world of higher education and research is subject today, evaluation in scientific journals is crucial for its impact on the individual and collective research that the indicators used are intended to measure. All evaluation agencies and bodies are concerned with this, but modes of evaluation differ to a greater or lesser extent between countries, as regards both evaluators and procedures and the criteria that are applied. These may also vary depending on the discipline concerned. All have advantages and drawbacks, and all are the subject of debate. The purpose of this dossier is to give an account of the practices currently followed on the one hand in a group of European countries, namely the United Kingdom, France, Germany, Spain, Italy and Portugal, and on the other hand in the USA, and to debate their respective merits. The contributors have all held important positions in evaluation bodies and as peer reviewers.